2015
DOI: 10.1002/jbm.a.35420
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparative survey of cell adhesion and proliferation of human induced pluripotent stem cells on surfaces of polymeric electrospun nanofibrous and solution‐cast film scaffolds

Abstract: Extracellular matrix (ECM) components play a critical role in regulating cell behaviors. Interactions between ECM components and cells are important in various biological processes, including cell attachment, survival, morphogenesis, spreading, proliferation, and gene expression. In this study the in vitro responses of human induced pluripotent stem cells (hiPSCs) on polycaprolactone (PCL) electrospun nanofibrous scaffold were reported in comparison with those of the cells on corresponding solution-cast film s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Hoveizi et al, have recently compared the cell adhesion and proliferation behavior of human iPSCs on polycaprolactone (PCL) electrospun nanofibrous scaffolds with solution-cast film scaffolds, to understand the interactions between ECM mimicking nanomaterials and cells. 3 The results of this study demonstrated that the nanofibrous scaffolds showed better support for the attachment and proliferation emphasizing on the sensing ability of human iPSCs in regard to the physical properties and chemical composition of the nanomaterial. 3 Similarly, Liu et al, have employed the potential of iPSCs in 3D PCL/gelatin scaffolds for chondrogenesis and articular cartilage defect restoration.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Hoveizi et al, have recently compared the cell adhesion and proliferation behavior of human iPSCs on polycaprolactone (PCL) electrospun nanofibrous scaffolds with solution-cast film scaffolds, to understand the interactions between ECM mimicking nanomaterials and cells. 3 The results of this study demonstrated that the nanofibrous scaffolds showed better support for the attachment and proliferation emphasizing on the sensing ability of human iPSCs in regard to the physical properties and chemical composition of the nanomaterial. 3 Similarly, Liu et al, have employed the potential of iPSCs in 3D PCL/gelatin scaffolds for chondrogenesis and articular cartilage defect restoration.…”
Section: Introductionmentioning
confidence: 74%
“…3 The results of this study demonstrated that the nanofibrous scaffolds showed better support for the attachment and proliferation emphasizing on the sensing ability of human iPSCs in regard to the physical properties and chemical composition of the nanomaterial. 3 Similarly, Liu et al, have employed the potential of iPSCs in 3D PCL/gelatin scaffolds for chondrogenesis and articular cartilage defect restoration. 4 This study demonstrated higher expression levels of chondrogenic markers in iPSCs than the control groups.…”
Section: Introductionmentioning
confidence: 74%
“…While a hierarchical organization can address the insufficiency of bulk properties, the nano-scale structure in the hierarchical structure tended to affect the adhesion, spreading and later proliferation of progenitor cells. 29 Besides the improvement in the proliferation rate, the most intuitive distinction was seen on the spreading pattern and cytoskeleton organization of cells seeded on the micro-nano scaffold, where a more stretched cytoskeleton of bone mesenchymal stem cells (BMSCs) was observed. The coordination of the micron structure and nanofibrous network can have an impact on the cellmaterial interaction pattern, potentially involving the activity of integrin, 30,31 vinculin 32 and Yes-associated protein (YAP), 33 all of which have been reported to regulate the cell-matrix interaction mediated by mechanical or structural cues presented by the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of natural and synthetic polymers such as polycaprolactone (PCL), poly( l ‐lactide‐co‐glycolide) (PLGA), collagen, and fibrin have been used in numerous studies to fabricate tissue‐engineering scaffolds. Among these polymers, PCL has been regarded as one of the most suitable materials for biomedical applications, owing to its biocompatibility, biodegradability and non‐toxicity . However, hydrophobic property of PCL leads to poor affinity for cell adhesion .…”
Section: Introductionmentioning
confidence: 99%
“…Among these polymers, PCL has been regarded as one of the most suitable materials for biomedical applications, owing to its biocompatibility, biodegradability and non-toxicity. [23][24][25] However, hydrophobic property of PCL leads to poor affinity for cell adhesion. 26,27 Plasma treatment and immobilization with natural polymers have been used increasingly to modify the surface chemistry of biomaterials with the aim of enhancing cellular responses and promoting desirable cell phenotypes.…”
Section: Introductionmentioning
confidence: 99%